Synthesis and testing of defected g-C3N4 with improved photocatalytic activity. Issue 1 (February 2020) - Zheng, Y; Li, C H; Cai, Y Y
Abstract: Graphitic carbon nitride samples with defected structure but larger surface areas were synthesized by adding urea as additive to the thermal decomposition (pyrolysis) of melamine. The pyrolysis was carried out at 600°C in ope-air conditions for 2 hours. The as-prepared samples were compared through detailed characterizations such as SEM, BET, XRD, XPS, FTIR and DRS. It was found out that the addition of urea functioned against the perfection of polymerization, and led to defected structure, which were suggested to be g-C3N4 segments in small crystalline domains. As a result, the formation of the defected structure led to blue-shifts in the optical transitions in the UV-Vis spectral range, as well as larger surface areas. In addition, the photocatalytic activities of the samples were measured by degrading Rhodamine B (RhB) with a concentration of 10 mg/L. It was found out that the samples with defected structure exhibited improved photocatalytic activity.